2016
DOI: 10.3168/jds.2015-10822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rumen-protected methionine, lysine, and histidine on lactation performance of dairy cows

Abstract: The objective of this study was to evaluate the effects of supplementing a metabolizable protein (MP)-deficient diet with rumen-protected (RP) Met, Lys, and His, individually or combined, on the performance of lactating dairy cows. The experiment was a 9-wk randomized complete block design with 72 Holstein cows. Following a 2-wk covariate period, cows were blocked by days in milk, milk yield, and parity, and randomly assigned to 1 of the following 6 treatments: (1) MP-adequate diet [MPA; +243g/d MP balance, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
121
5
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 93 publications
(159 reference statements)
22
121
5
4
Order By: Relevance
“…If, in fact, greater p -AKT: AKT reflected enhanced insulin signaling within mammary tissue, the lower (P < 0.05; Table 3) plasma concentrations of NEAA (Tucker et al, 2017), along with lower His (P < 0.05; Table 3; Giallongo et al, 2016) in response to Met might have contributed to promoting greater rates of milk protein synthesis (Batistel et al, 2017). The positive effect of insulin on milk protein percentage and yield during euglycemia in mid to late lactation has been reported previously (McGuire et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…If, in fact, greater p -AKT: AKT reflected enhanced insulin signaling within mammary tissue, the lower (P < 0.05; Table 3) plasma concentrations of NEAA (Tucker et al, 2017), along with lower His (P < 0.05; Table 3; Giallongo et al, 2016) in response to Met might have contributed to promoting greater rates of milk protein synthesis (Batistel et al, 2017). The positive effect of insulin on milk protein percentage and yield during euglycemia in mid to late lactation has been reported previously (McGuire et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the NRC (2001) model, the MP balance in cows fed FPAA averaged −407 g/d, and was 150% less than that in cows fed CSBAA (−163 g/d; Table 7). Lee et al (2012) and Giallongo et al (2016) showed that His appears to be the third-limiting AA after Lys and Met in MP-deficient diets, which ranged from −22 to −385 g/d in their experiments.…”
Section: Plasma Concentration Of Aamentioning
confidence: 91%
“…Therefore, the duodenal His flow is likely to be relatively low in diets with low grain or protein supplementation that rely heavily on microbial protein synthesis for MP supply. Such diets are typical for low-protein diets based either on grass (Kim et al, 1999;Vanhatalo et al, 1999) or corn silage (Lee et al, 2012;Giallongo et al, 2016). Lapierre et al (2014b) reported that graded abomasal His infusions (0, 7.6, 15.2, and 22.8 g/d) elicited a dose-response increase in plasma His concentration, but the marginal response of plasma His concentration decreased as the rate of His infusion increased.…”
Section: Casein Infusion and Responses Of Plasma Group 1 Aa Group 2 mentioning
confidence: 99%